2006
DOI: 10.1002/ajpa.20392
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of female black howler monkey (Alouatta Pigra) responses to loud calls from potentially infanticidal males: Effects of numeric odds, vulnerable offspring, and companion behavior

Abstract: During group defense, the contribution of female black howler monkeys (Alouatta pigra) may help deter male intruders; however, their involvement during natural intergroup encounters is facultative. Experimental playback trials simulating potentially infanticidal males were used to examine whether a female's reproductive investment and/or her group's relative fighting ability would influence her participation in loud call displays. Female howlers never responded to recordings without alpha male accompaniment, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 59 publications
(62 reference statements)
2
48
0
4
Order By: Relevance
“…Strong male agonistic behavior toward foreign groups, with low female participation, observed in other howler species (Alouatta pigra, A. seniculus arctoidea : Kitchen 2006;Sekulic 1983) also supports the hypothesis that roars act as an aggressive display more related to mate competition than to food competition.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Strong male agonistic behavior toward foreign groups, with low female participation, observed in other howler species (Alouatta pigra, A. seniculus arctoidea : Kitchen 2006;Sekulic 1983) also supports the hypothesis that roars act as an aggressive display more related to mate competition than to food competition.…”
Section: Discussionsupporting
confidence: 66%
“…Our results do not support any of these predictions: females brown and blackand-gold howlers with unweaned infants do not differ from other adult females in their probability of roaring. A study of Alouatta pigra shows similar results and suggests that the best predictor for female participation in aggressive intergroup interactions is not the presence of unweaned infants, but the number of males in their group in relation to the number of males in an intruding group as simulated by playbacks: Females do not participate when the numeric odds are against their group, demonstrating that females were able to assess the group fighting ability through the roars and decide when to participate or not (Kitchen 2006). Thus, the presence of unweaned infants seems not to be a predictor of the female participation in roaring bouts.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Researchers in these fields have found that the ability to discriminate between different numbers of objects appears to be a foundational cognitive ability and have documented this ability in numerous species across the Animal Kingdom. For example, quantity discrimination has been demonstrated experimentally in several species of fish [5,11,[19][20][21], amphibians [8,22,23], birds [18,[24][25][26][27][28][29][30][31][32][33][34][35], mammals [9,[36][37][38][39][40][41], primates [42][43][44][45], human infants [46][47][48][49] and even some invertebrates [50][51][52]. The only study testing quantity discrimination in a reptile found that although ruin lizards (Podarcis sicula) do spontaneously select the larger quantity of food, they do not spontaneously select the option with a higher number of food items [53].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore loud calls by novel groups within or close to a territory may frequently elicit vocal responses. In contrast, the grouping and social behaviors of Alouatta is more varied, with single and multi-male groups, overlapping territories and intragroup dominance hierarchies (Whitehead, 1987;Kitchen, 2006;Hopkins, 2013), thus responses to playbacks simulating the presence of an unknown individual may also be more varied.…”
Section: Andrea Salcedo R Manuel Mejia Katie Slocombe Sarah Papworthmentioning
confidence: 99%